2015
DOI: 10.1128/mbio.00616-15
|View full text |Cite
|
Sign up to set email alerts
|

HAMP Domain Rotation and Tilting Movements Associated with Signal Transduction in the PhoQ Sensor Kinase

Abstract: HAMP domains are α-helical coiled coils that often transduce signals from extracytoplasmic sensing domains to cytoplasmic domains. Limited structural information has resulted in hypotheses that specific HAMP helix movement changes downstream enzymatic activity. These hypotheses were tested by mutagenesis and cysteine cross-linking analysis of the PhoQ histidine kinase, essential for resistance to antimicrobial peptides in a variety of enteric pathogens. These results support a mechanistic model in which peripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 59 publications
6
49
3
Order By: Relevance
“…It has been suggested that the HAMP domain regulates the phosphorylation of homodimeric sensor proteins by transmitting the conformational changes in the ligand-binding domains to the C-terminal signaling kinase domains (Aravind and Ponting, 1999; Klose et al, 2014; Schultz et al, 2015). This model is supported by genetic and biochemical studies (Zhou et al, 2009; Matamouros et al, 2015). …”
Section: Fungal Histidine Kinases Linked To Phenylpyrrole Resistancementioning
confidence: 69%
“…It has been suggested that the HAMP domain regulates the phosphorylation of homodimeric sensor proteins by transmitting the conformational changes in the ligand-binding domains to the C-terminal signaling kinase domains (Aravind and Ponting, 1999; Klose et al, 2014; Schultz et al, 2015). This model is supported by genetic and biochemical studies (Zhou et al, 2009; Matamouros et al, 2015). …”
Section: Fungal Histidine Kinases Linked To Phenylpyrrole Resistancementioning
confidence: 69%
“…We therefore propose that distinct conformational inputs result from binding of cognate AIPs to the sensor domains of each AgrC subgroup. Testing this idea will require additional biochemical study, perhaps involving crosslinking approaches (Matamouros et al, 2015; Molnar et al, 2014; Saita et al, 2015; Wang et al, 2014), although high-resolution structural information on the system will ultimately be needed to fully understand these inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Support for functionally relevant changes in helical supercoiling within the coiled‐coil linker derives from both biochemical data and structural analyses. In several systems, sequence and length variations of the linker implied its coiled‐coil structure and signal‐dependent changes in α‐helical supercoiling . For the present scope, ample data on the blue‐light‐responsive LOV histidine kinase YF1 are most relevant .…”
Section: Signal Transmission Through α‐Helical Bundles and Linkersmentioning
confidence: 90%